Soil-water Modelling Framework Using Pedostructure and Structural Representative Elementary Volume (SREV) Concepts - Braudeau , Erik; Mohtar , Rabi H. (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 2, 2023)
Current soil water models do not account for the internal organization of the soil medium, and thus ignore the physical interaction between the water film at the surface of the solids that form the soil structure and the structure itself. Current models, therefore, deal empirically with the physical soil qualities, which are all a result of the interaction between soil water and soil structure. Since all processes in the soil medium are thermodynamically connected to the soil water cycle, this circumstance restricts the modelling and coupling of the various processes taking place in the soil medium. The goal of this article is to present a comprehensive framework for characterizing and modelling the internal soil organization and its hydrostructural properties as a result of the structure's interaction with soil water storage and dynamics. The paper extends the pedostructure concept, which enabled the incorporation of soil structure into equations of water equilibrium and movement in soils. It presents new soil-water thermodynamic concepts developed in the context of the Structural Representative Elementary Volume concept (SREV). There was excellent agreement between the Yolo loam soil profile's simulated drainage after infiltration and the measured moisture profile. With the understanding that the soil's hydrostructural organization and the resulting thermodynamic properties serve as the basis for such coupling, this novel modelling framework offers up new opportunities for agro-environmental models to be coupled with the soil medium.